1987
DOI: 10.1021/bi00400a023
|View full text |Cite
|
Sign up to set email alerts
|

Antenna organization in green photosynthetic bacteria. 1. Oligomeric bacteriochlorophyll c as a model for the 740 nm absorbing bacteriochlorophyll c in Chloroflexus aurantiacus chlorosomes

Abstract: Bacteriochlorophyll (BChl) c was extracted from Chloroflexus aurantiacus and purified by reverse-phase high-pressure liquid chromatography. This pigment consists of a complex mixture of homologues, the major component of which is 4-ethyl-5-methylbacteriochlorophyll c stearyl ester. Unlike previously characterized BChls c, the pigment from C. aurantiacus is a racemic mixture of diastereoisomers with different configurations at the 2a chiral center. Diluting a concentrated methylene chloride solution of BChl c w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
117
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 168 publications
(125 citation statements)
references
References 35 publications
8
117
0
Order By: Relevance
“…We observed that the CD intensity of low-light chlorosomes only doubled upon treatment with proteinase K compared to a fivefold increase in the high-light chlorosomes. There is some evidence that BChl c in the chlorosome is organized as oligomers [8,9], which may be bound to protein in order to maintain parallel transition moments between clusters of BChl c [2.5,26]. There are several reports that BChl c aggregates in hexane [27,28], in aqueous suspension, or after LDS treatment [4], and after proteolytic treatment [4,18] exhibited higher rotational strength than BChl c in chlorosomes of ChlorojZexus auruntiucus.…”
Section: Discussionmentioning
confidence: 99%
“…We observed that the CD intensity of low-light chlorosomes only doubled upon treatment with proteinase K compared to a fivefold increase in the high-light chlorosomes. There is some evidence that BChl c in the chlorosome is organized as oligomers [8,9], which may be bound to protein in order to maintain parallel transition moments between clusters of BChl c [2.5,26]. There are several reports that BChl c aggregates in hexane [27,28], in aqueous suspension, or after LDS treatment [4], and after proteolytic treatment [4,18] exhibited higher rotational strength than BChl c in chlorosomes of ChlorojZexus auruntiucus.…”
Section: Discussionmentioning
confidence: 99%
“…Purified BChl c forms oligomers in hexane with the Q y absorption peak at ∼740 nm, about 70 nm red-shifted from that of its monomeric form as observed in methanol, and the absorption spectra closely resemble that of BChl c in chlorosomes. 16,17 In addition to the 740 nm oligomer, there are at least two other aggregates formed in CH 2 Cl 2 , CHCl 3 , and CCl 4 (or benzene) with absorption maxima at 680 and 710 nm for R-type BChl c. 8,18,19 The 710 nm species is reported to exhibit unusual spectroscopic properties, in particular an intense fluorescence emission. 8,20 A large number of studies have been made to elucidate the structure of the 740 nm aggregate in relation with the organization of BChl c in chlorosomes.…”
Section: Introductionmentioning
confidence: 99%
“…16,17 In addition to the 740 nm oligomer, there are at least two other aggregates formed in CH 2 Cl 2 , CHCl 3 , and CCl 4 (or benzene) with absorption maxima at 680 and 710 nm for R-type BChl c. 8,18,19 The 710 nm species is reported to exhibit unusual spectroscopic properties, in particular an intense fluorescence emission. 8,20 A large number of studies have been made to elucidate the structure of the 740 nm aggregate in relation with the organization of BChl c in chlorosomes. [8][9][10][11]16,17,[21][22][23] Descriptions of the large aggregation structure have converged into two basic models 3 in which the BChl c molecules are arranged in antiparallel or parallel chains.…”
Section: Introductionmentioning
confidence: 99%
“…In vitro assembly studies in aqueous buffers have also suggested that hydrophobic carotenoids may augment self-assembly of BChls into aggregates by enhancing interaction between the hydrophobic tails of esterifying alcohols within lamellae (18,19). Furthermore, carotenoids can be extracted from chlorosomes isolated from several species by nonpolar solvents, such as hexane (9,20). Structural characterization of hexane-treated chlorosomes from Chlorobium phaeovibrioides (containing BChl e as the main pigment) demonstrated that carotenoids are located within lamellae and increase the apparent spacing between adjacent lamellar layers (9).…”
mentioning
confidence: 99%